Los mallorquines / Josep Melia ; [traducción y notas, Gabriel Cisneros ; prólogo, Joan Fuster] - Cisneros, GabrielFuster, Joan (1922-1992); Melià, Josep (1939-2000) (Divulgacion Universitaria; 9. La pell de Brau)
Bibliografía: p. 254-256